Analysis of the Implementation of Pasundanan Characteristics of Education in Improving School Image and Competitiveness - Heri Erlangga; Gending Raspuzi; Undang Juju; Yusuf Arifin (Universitas Negeri Makassar, 2026)
This research is motivated by the issue of the ineffectiveness of school management in implementing Pasundan-style character education for Pasundan Junior High School students in Bandung City in order to improve the school's image and competitiveness. The results of the observation show that Pasundan-style character education has not been well absorbed by Pasundan Junior High School students in Bandung City, which is indicated by the public's perception of the school's image and competitiveness which is still low compared to other leading schools in Bandung City. The focus of the research is to examine the implementation of educational management, especially regarding Pasundan-style character education based on religion and culture at Pasundan Junior High School. The formulation of the problem is how the implementation of Pasundan-style character education management in Pasundan Junior High School in Bandung City, how the performance achieved in the implementation of Pasundan-style character education, what are the obstacles faced in the implementation of Pasundan-style character education, and what are the strategies to increase the effectiveness of Pasundan-style character education implementation in improving the school's image and competitiveness. The research uses a qualitative approach with a case study research method. The data analysis technique uses an interactive model analysis. Data collection techniques are carried out through literature studies and field studies by means of observation, and in-depth interviews with informants who are considered representative. The results of the study indicate that the management of Pasundan Characteristics Education in Pasundan Middle Schools in Bandung City has been implemented quite well, however, its implementation has not been optimal and still experiences various obstacles, obstacles in the implementation of Pasundan education can be classified into several large categories that interact with each other, namely obstacles originating from the dimensions of human resources, curricular and pedagogical obstacles, structural and managerial obstacles, cultural and social obstacles, obstacles originating from external pressures and environmental changes, as well as obstacles related to limited material and financial resources, the competitiveness performance of Pasundan Middle Schools in Bandung City shows a relatively good condition in all dimensions studied and finally the strategy to increase the effectiveness of the implementation of Pasundan Characteristics education management in improving the image and competitiveness of schools is prepared by maximizing and elaborating the parameters of educational management functions, namely planning, organizing, actuating, and controlling which are associated with the characteristics of Pasundan Middle Schools in Bandung City.